A Determination Method of Optimal Customization Degree of Logistics Service Supply Chain with Mass Customization Service - Weihua Liu; Qian Wang; Donglei Zhu; Yang Liu (Discrete Dynamics in Nature and Society)
Customization degree is a very important field of mass customization. Its improvement could enhance customer satisfaction and further increase customer demand while correspondingly it will increase service price and decrease customer satisfaction and demand. Therefore this paper discusses how to deal with such issues in logistics service supply chain (LSSC) with a logistics service integrator (LSI) and a customer. With the establishment of customer demand function for logistics services and profit functions of the LSI and the customer, three different decision modes are proposed (i.e., customization degree dominated by LSI, customization degree dominated by customer, and customization degree decided by concentrated supply chain); many interesting findings are achieved. Firstly, to achieve customization cooperation between LSI and customer, measures should be taken to make the unit increase cost of the customized logistics services lower than a certain value. Secondly, there are differences between the optimal customization degree dominated by LSI and that dominated by customer. And in both cases, the dominator could realize more profit than the follower. Thirdly, with the profit secondary distribution strategy, the modified decentralized decision mode could accomplish the maximum profit achieved in centralized decision mode and meanwhile get the optimal customization degree.